2015
DOI: 10.1557/mrc.2015.52
|View full text |Cite
|
Sign up to set email alerts
|

Screen-printed organic electrochemical transistors for metabolite sensing

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 25 publications
2
47
0
Order By: Relevance
“…Screen-printing has also been successfully used for the fabrication of OECTs-based biosensors. In 2015, Scheiblin et al [111] reported on the fabrication of glucose and lactate sensors on a flexible, plastic substrate (polyethylene naphthalate, PEN). These devices were obtained by using three different inks: PEDOT:PSS (fabrication of the transistors active channel, final thickness of 500 nm), poly(vinylidene fluoride) (PVDF, a dielectric material used to insulate the electrical contacts and define the contact area between the channel and the electrolyte, final thickness of 2 µm) and finally a silver-based ink (used to realize the electrical contacts, final thickness of approximately 8 µm).…”
Section: Screen-printingmentioning
confidence: 99%
See 2 more Smart Citations
“…Screen-printing has also been successfully used for the fabrication of OECTs-based biosensors. In 2015, Scheiblin et al [111] reported on the fabrication of glucose and lactate sensors on a flexible, plastic substrate (polyethylene naphthalate, PEN). These devices were obtained by using three different inks: PEDOT:PSS (fabrication of the transistors active channel, final thickness of 500 nm), poly(vinylidene fluoride) (PVDF, a dielectric material used to insulate the electrical contacts and define the contact area between the channel and the electrolyte, final thickness of 2 µm) and finally a silver-based ink (used to realize the electrical contacts, final thickness of approximately 8 µm).…”
Section: Screen-printingmentioning
confidence: 99%
“…If the previous example used GOx in solution, in almost all recent publications, GOx was immobilized within the device structure, preventing enzyme leakage and decrease of signal over time. For example, Malliaras and coworkers developed a screen-printed OECT for both glucose and lactate sensing [111]. Rather than being present in solution, both the ferrocene mediator, which was covalently bound to chitosan, and the GOx were integrated into the sol-gel electrolyte which prevented their further deterioration during measurements.…”
Section: Glucosementioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Of the many electronic devices utilizing organic semiconductors, organic thin-film transistors (OTFTs) have in recent years become important components of large-area flexible displays as well as of radio-frequency identification tags, logic circuits, smart cards, and chemical sensors. [1][2][3][4] Of the many electronic devices utilizing organic semiconductors, organic thin-film transistors (OTFTs) have in recent years become important components of large-area flexible displays as well as of radio-frequency identification tags, logic circuits, smart cards, and chemical sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Due to easy fabrication and CPs processability, OECTs found application in printed electronics, for the production of displays and biosensors. [29][30][31][32] Additionally, low operating voltages, stability in aqueous environment, and capability of interfacing ionic and electronic signals make them suitable devices for bioelectronics and healthcare applications. 33,34 However, despite their great success, OECTs currently suffer of many drawbacks, which limit their use for practical applications.…”
Section: Chapter 3 Electrochemical Transistorsmentioning
confidence: 99%